2022
DOI: 10.1186/s13148-022-01249-z
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of accelerated epigenetic aging of breast tissues in patients with breast cancer is driven by CpGs associated with polycomb-related genes

Abstract: Purpose Age is one of the strongest risk factors for the development of breast cancer, however, the underlying etiology linking age and breast cancer remains unclear. We have previously observed links between epigenetic aging signatures in breast/tumor tissue and breast cancer risk/prevalence. However, these DNA methylation-based aging biomarkers capture diverse epigenetic phenomena and it is not known to what degree they relate to breast cancer risk, and/or progression. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…The data sources used by these studies included Komen Breast Tissue Bank ( 26 , 28 ), the prospective cohort Sister Study ( 25 , 27 ), National Cancer Institute Genomic Data Commons ( 24 ), and samples from clinical settings ( 24 ). The study of the Sister Study ( 25 ) had the largest sample sizes of N=2,764.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data sources used by these studies included Komen Breast Tissue Bank ( 26 , 28 ), the prospective cohort Sister Study ( 25 , 27 ), National Cancer Institute Genomic Data Commons ( 24 ), and samples from clinical settings ( 24 ). The study of the Sister Study ( 25 ) had the largest sample sizes of N=2,764.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 10 different epigenetic clocks were used ( Table 1 ). The Horvath clock was most frequently used appearing in three of the five studies ( 24 26 ). The included studies found that DNAm age from the following epigenetic clocks had a statistically significant association with breast cancer: Hannum ( 25 ), Horvath ( 25 ), Levine ( 25 , 26 ), GrimAge ( 25 , 27 ), DNAmAge ( 28 ), and Yang ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With regards to the alterations—acceleration or deceleration—observed in the clocks, various associations have been investigated, particularly the aforementioned links with environmental factors and disease (Fransquet et al, 2019 ; Levine et al, 2018 ; Lu et al, 2019 ; Marioni et al, 2015 ; Oblak et al, 2021 ), to ascertain whether the DNAm alterations which occur during these processes could drive the changes observed in the clocks. For instance, a recent study investigating DNAm age acceleration in the non‐tumoral breast tissue of breast cancer patients demonstrated that the observed alteration in the epigenetic clock could be explained by a subset of the clock CpGs that suffer from the well‐known cancer‐associated hypermethylation of Polycomb associated loci (Rozenblit et al, 2022 ). Indeed, clocks have been constructed which partly reflect the DNAm alterations induced by cancer‐related lifestyle factors such as smoking (Lu et al, 2019 ).…”
Section: Dna Methylation Clocks As New Tools In the Study Of Diseasementioning
confidence: 99%
“…Finally, Liu et al investigate the impact of ethnicity on DNA methylation changes in peripheral blood cells from breast cancer (BC) patients. Age is one of the strongest risk factors for the development of BC, and evidence shows accelerated epigenetic aging in normal breast tissues adjacent to breast tumors in BC patients ( Hofstatter et al, 2018 ; Rozenblit et al, 2022 ). DNA methylation signatures have been identified in the white blood cells as potential biomarkers for BC.…”
mentioning
confidence: 99%